2007
DOI: 10.2298/jsc0712271p
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of the lectin of the marine coral Gerardia savaglia by marine quinone avarone

Abstract: The quinone avarone, isolated from the marine sponge Dysidea avara, possesses the ability to chemically modify proteins. In this work, modification of lectin isolated from the coral Gerardia savaglia by avarone was examined. The techniques used for studying the modification were: SDS PAGE, isoelectric focusing and hemagglutination testing. The results of the SDS PAGE indicate dimerization of the protein. A shift of the pI toward lower value occurs upon modification. The change of the hemagglutination activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In previous studies it was shown that avarone, its derivatives and related quinones modified lysine residues in proteins by nucleophilic addition. 17,18,26 There are 6 such residues in this structure: Lys1, Lys13, Lys33, Lys96, Lys97 and Lys116. While all of them are remote enough from the active site of the enzyme, it seems that some are less available for covalent interactions than others.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies it was shown that avarone, its derivatives and related quinones modified lysine residues in proteins by nucleophilic addition. 17,18,26 There are 6 such residues in this structure: Lys1, Lys13, Lys33, Lys96, Lys97 and Lys116. While all of them are remote enough from the active site of the enzyme, it seems that some are less available for covalent interactions than others.…”
Section: Resultsmentioning
confidence: 99%